Developing a Design Model for Seven Charm (Sapta Pesona ) Tourism Awareness in the Local Community of Lake Toba - Iskandar, Eddy; Taib, Zulkifli; Septriawan, M. Reza (Tradition and Modernity of Humanity, 2022)
Lake Toba is one of the government's five proposed super tourism locations. Strengthening the tourist sector is a key component of a region's national development strategy. The tourist sector was chosen to be strengthened because it has the potential to boost the Indonesian economy. As for the real battle in managing Lake Toba tourism in terms of human resources, citizens' understanding of tourism is still limited, the model of service to tourists is still lacking, tourist attractions that have not been maintained on a consistent basis tend to emphasize nature and neglect cultural attractions, and insufficient infrastructure such as road access. The goal of this research is to determine the local community of Toba Regency's willingness to participate in the development of Lake Toba tourism and the ability of the local community's great service abilities to attract tourists. This study takes a qualitative-exploratory strategy, stressing characteristics of enrichment in the field as a research force through data gathering approaches such as surveys, literature reviews, finding specific cases and selecting goals, data collection, data analysis, and conclusion. The technique for developing an ideal tourist plan is based on Jacqueline M. Stavros' SOAR model, a combination of SWOT analysis and Appreciative Inquiry (AI). This approach entails all stakeholder groups in order to collect data on the strengths, opportunities, goals, and outcomes of the Lake Toba tourism planning model in the Toba district.